Spatial Data Inventory and Collaboration System: A Web-GIS Development and Outreach Approach for Matesih Digital Village - Yusfia Hafid Aristyagama; Cucuk Wawan Budiyanto; Nurcahya Pradana Taufik Prakisya; Puspanda Hatta; Febri Liantoni; Rosihan Ari Yuana (LKP KARYA PRIMA KURSUS, 2026)
Developing the potential of foster villages is often hindered by a lack of valid and integrated field data. Matesih Village in Karanganyar Regency possesses significant natural and economic potential, yet it remains under-explored by the research community. This study aims to develop a web-based GIS application as a spatial mapping medium for village potentials and problems to initiate the